Manual Hydraulic Briquetting Machine for Sustainable Fuel Production from Biomass and Charcoal Dust - Umar, Saminu; Hauwa’u Umar (UIR PRESS, 2026)
Access to reliable and affordable energy remains a significant challenge in rural communities, where reliance on firewood, charcoal and kerosene contributes to environmental degradation and health risks. This study reports the design, fabrication and testing of a manual hydraulic briquetting machine capable of converting locally available biomass and charcoal dust into dense, uniform briquettes. The machine was constructed from mild steel and a hydraulic bottle jack, allowing operation without electricity and simple maintenance using local tools. Briquette production involved mixing biomass with cassava starch as a binder, then manually compressing and air-drying. Compressive strength tests showed that charcoal dust produced the strongest briquettes (1.30 KNm-²), followed by rice husk (1.10 KNm-²) and sawdust (1.03 KNm-²), indicating that feedstock properties influence briquette performance. The results indicate that the machine provides a low-cost, sustainable fuel option while promoting effective utilisation of biomass and charcoal by-products.